2011
DOI: 10.1016/j.bmcl.2011.01.128
|View full text |Cite
|
Sign up to set email alerts
|

On the function of the internal cavity of histone deacetylase protein 8: R37 is a crucial residue for catalysis

Abstract: Biochemical studies reveal that a conserved arginine residue (R37) at the centre of the 14 Å internal cavity of histone deacetylase (HDAC) 8 is important for catalysis and acetate affinity. Computational studies indicate that R37 forms multiple hydrogen bonding interactions with the backbone carbonyl oxygen atoms of two conserved glycine residues, G303 and G305, resulting in a ‘closed’ form of the channel. One possible rationale for these data is that water or product (acetate) transit through the catalyticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 20 publications
3
48
0
Order By: Relevance
“…The role of Arg37 in HDAC8 was experimentally validated with mutagenesis studies, which demonstrated that an arginine side chain is crucial for catalytic activity and acetate binding affinity [90]. These results are consistent with the mutagenesis experiments performed on HDAC1 [87], which confirm the crucial role of this residue in catalysis.…”
Section: A-amino-ketone-containing Hdacissupporting
confidence: 66%
“…The role of Arg37 in HDAC8 was experimentally validated with mutagenesis studies, which demonstrated that an arginine side chain is crucial for catalytic activity and acetate binding affinity [90]. These results are consistent with the mutagenesis experiments performed on HDAC1 [87], which confirm the crucial role of this residue in catalysis.…”
Section: A-amino-ketone-containing Hdacissupporting
confidence: 66%
“…Although R37 is conserved as R506 in HDAC6 CD2, making similar contacts to the loop preceding the catalytic tyrosine as in HDAC8, it does not appear to serve as a channel gate in HDAC6 CD2, as proposed for HDAC8. 22 Instead, R506 simply stabilizes the conformation of the glycine-rich loop of HDAC6 CD2 through hydrogen bonding. In doing so, this conserved arginine may simply function to stabilize the position of the catalytic tyrosine.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 These hydrogen bonds, along with a van der Waals contact between the carbonyl of G139 and the amide nitrogen of G303, are believed to lock the channel gate closed. 22 Additionally, a water molecule, referred to as the “bridging water molecule”, forms hydrogen bonds with R37, W137, G139, and G303 in wild-type HDAC8. Since opening the gate would require reorganization of this hydrogen bond network, it is possible that the potential flexibility afforded by the glycine-rich loop enables egress of the acetate product as well as dissociation of the L-lysine product.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic functions of these histidine residues are influenced by hydrogen bonds with D176 and D183, respectively. While H142 was initially proposed to be the general base [13, 31], this proposal is not supported by the residual activity and pH-rate dependence of H142A HDAC8 [37]. Furthermore, the K + -dependence of catalytic activity in H142A, D176A, and D176N HDAC8 mutants suggests that H142 serves as a general electrostatic catalyst [32••].…”
Section: Catalytic Mechanismmentioning
confidence: 99%
“…Thus, H143 serves as a general base-general acid catalyst (SL Gantt, PhD thesis, University of Michigan, 2006). Product acetate is initially coordinated to Zn 2+ , as exemplified by the structure of the HDAH-acetate complex [23], and may subsequently exit through an internal channel [37]. …”
Section: Catalytic Mechanismmentioning
confidence: 99%